The BGR contingency model for leading change. (15th March 2012) - Brown, Derek R.; Gordon, Raymond; Rose, Dennis Michael
The continuing failure rates of change initiatives, combined with an increasingly complex business environment, have created significant challenges for the practice of change management. High failure rates suggest that existing change models are not working, or are being incorrectly used. A different mindset to change is required. The BGR Contingency Model (named after the authors&#39 surnames) for leading change facilitates the required mindset, and addresses the issue of leadership decision–making as one of the major contributors to high change initiative failure rates. Drawing on four propositions offered, the conceptual model is based on the interdependency of ethics and logic in leadership decision–making in change initiatives. The model has specific, formal checkpoints of this interdependency. Its basic design is a series of progressions, or groups of tasks, which start with the strategic and continue through the operational to the tactical levels of the organisation, in an iterative fashion.